Characterization of the Zebrafish Cell Landscape at Single-Cell Resolution - Jiang, Mengmeng; Xiao, Yanyu; E, Weigao; Ma, Lifeng; Wang, Jingjing; Chen, Haide; Gao, Ce; Liao, Yuan; Guo, Qile; Peng, Jinrong; Han, Xiaoping; Guo, Guoji (Frontiers in Cell and Developmental Biology, 2021)
Zebrafish have been found to be a premier model organism in biological and regeneration research. However, the comprehensive cell compositions and molecular dynamics during tissue regeneration in zebrafish remain poorly understood. Here, we utilized Microwell-seq to analyze more than 250,000 single cells covering major zebrafish cell types and constructed a systematic zebrafish cell landscape. We revealed single-cell compositions for 18 zebrafish tissue types covering both embryo and adult stages. Single-cell mapping of caudal fin regeneration revealed a unique characteristic of blastema population and key genetic regulation involved in zebrafish tissue repair. Overall, our single-cell datasets demonstrate the utility of zebrafish cell landscape resources in various fields of biological research.